Changes in Low Back Muscle Activity and Spine Kinematics in Response to Smartphone Use During Walking. Issue 7 (1st April 2021) - Choi, Seobin; Kim, Misol; Kim, Eunjee; Shin, Gwanseob
Abstract : Study Design: Within-subject design of an experimental study. Objective: The aim of this study was to determine the effects of smartphone use on the activity level of the lumbar erector spinae muscles and spine kinematics during walking. Summary of Background Data: Using a smartphone while walking makes the user hold the phone steady and look downward to interact with the phone. Walking with this non-natural posture of the head and the arms may alter the spine kinematics and increase the muscular load on the low back extensor muscles. Methods: Twenty healthy young individuals participated in the laboratory experiment. Each participant walked on a treadmill in five different conditions: normal walking without using a phone, conducting one-handed browsing while walking, two-handed texting while walking, walking with one arm bound, and walking with both arms bound. Spine kinematics variables and the myoelectric activity levels of the lumbar erector spinae muscles were quantified and compared between the five walking conditions. Results: Participants walked with significantly ( P  < 0.05) more thoracic kyphosis and lumbar lordosis when using a phone compared to when walking without using the phone. The median level of muscle activity was also 16.5% (browsing) to 31.8% (texting) greater for the two smartphone use conditions than for the normal walking condition, and the differences were significant ( P  < .05). Between the normal walking and the two bound arm walking conditions, no significant difference in the muscle activity was found. Conclusion: Study results show that the concurrent use of a smartphone while walking could pose a larger muscular load to the lumbar erector spinae muscles than that of normal walking. Habitual use of a smartphone while walking could be a risk factor for low back musculoskeletal problems. Level of Evidence: N/A Abstract : This laboratory experimental study was to examine the effect of smartphone use during walking on the activity level of the low back extensor muscles and spine kinematic variables. The concurrent use of a smartphone affected thoracic and lumbar spine curvature and increased the muscle activity.